2022
DOI: 10.3389/fcell.2022.865948
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones Deficiency Impairs Male Germ Cell Development: A Cross Talk Between Hypothalamic-Pituitary-Thyroid, and—Gonadal Axes in Zebrafish

Abstract: In vertebrates, thyroid hormones are critical players in controlling different physiological processes such as development, growth, metabolism among others. There is evidence in mammals that thyroid hormones are also an important component of the hormonal system that controls reproduction, although studies in fish remain poorly investigated. Here, we tested this hypothesis by investigating the effects of methimazole-induced hypothyroidism on the testicular function in adult zebrafish. Treatment of fish with me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 99 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…The thyroid and stress axes have been extensively studied individually in relation to testis function (reviewed in [3,12,30,[33][34][35]; however, the interaction between them, particularly on gonadal sex fate,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thyroid and stress axes have been extensively studied individually in relation to testis function (reviewed in [3,12,30,[33][34][35]; however, the interaction between them, particularly on gonadal sex fate,…”
Section: Discussionmentioning
confidence: 99%
“…THs can affect gonadal development and function in vertebrates [33,[35][36][37][38][39]. Several studies have shown that hypothyroidism decreases plasma androgen levels in sh [35,40,41], birds [42,43], and mammals [37,44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation